Coal Bottom Ash for Portland Cement Production - Cristina Argiz; Miguel Ángel Sanjuán; Esperanza Menéndez (Advances in Materials Science and Engineering)
Because of industrialization growth, the amount of coal power plant wastes has increased very rapidly. Particularly, the disposal of coal bottom ash (CBA) is becoming an increasing concern for many countries because of the increasing volume generated, the costs of operating landfill sites, and its potential hazardous effects. Therefore, new applications of coal bottom ash (CBA) have become an interesting alternative to disposal. For instance, it could be used as a Portland cement constituent leading to more sustainable cement production by lowering energy consumption and raw material extracted from quarries. Coal fly and bottom ashes are formed together in the same boiler; however, the size and shape of these ashes are very different, and hence their effect on the chemical composition as well as on the mineralogical phases must be studied. Coal bottom ash was ground. Later, both ashes were compared from a physical, mechanical, and chemical point of view to evaluate the potential use of coal bottom ash as a new Portland cement constituent. Both ashes, produced by the same electrical power plant, generally present similar chemical composition and compressive strength and contribute to the refill of mortar capillary pores with the reaction products leading to a redistribution of the pore size.